Influências ambientais sobre o ecossistema halodule wrightii na costa semiárida do Brasil - Barros, Kcrishna Vilanova de Souza (2013)
Because of anthropogenic and climate change-related pressures, there is an increasing need of understanding on species-environment relationships. The objective of this study was to observe environmental influences on the variations of Halodule wrightii Ascherson in the semiarid coast of Brazil and the influences of these variations on florofaunal associations. In 2010, four meadows of H. wrightii were mapped and the influences of rocky and sandy bottoms and of the seasonality on shoot density, biometry and biomass were studied. It were also observed the influences of H. wrightii changes on macroalgal and macrofaunal communities, and also the main environmental influences, among metheorological, physicochemical and sedimentary variables, on the seagrass variations. The meadows were distributed in patches, parallel to the coastline, and more extensive on the sandy bottoms. The total area sampled was of 24430 m2 , being 5800 m2 composed of dense patches, 9100 m2 of sparse patches, 14000 m2 of nonvegetated areas, and 8000 m2 of rocks and other reef associations (algae, zoanthids, sponges and corals). The rocky habitats had meadows with greater shoot densities (DRY, t= -7,528; df = 43; p = 0,000; RAINY, t= - 11,038; df = 43; p = 0,000), biometry (DRY, t= -2,674; df = 47; p = 0,010; RAINY, t = - 0,172; df = 42; p = 0,863), and total biomass (DRY, t= -5,566; df = 58; p = 0,000; RAINY, t= -6,347; df = 58; p = 0,000). Eighteen species of macroalgae were identified, classified as epilithic (50%), epiphytes on H. wrightii (38.4%), epipsammics (8%), and epiphytes on other algae (4%). The descriptors of this community were directly correlated to the H. wrightii shoot density, increasing during the dry season, being more influenced by the habitat than seasonality (PerMANOVA, F= 29,4; R2 = 0,20; p < 0,001). The macrofauna was composed by 1108 specimens belonging to 112 taxa, highlighted crustaceans, mollusks and polichaetes. The faunistic diversity increased during the dry season probably due to an input of infauna because of the increase in hydrodynamic, but the abundance of epifauna seemed directly related to the seagrass variations. Considering the seagrass habitats, the faunal descriptors were significantly higher in the meadows of rocky bottoms, and correlated to H. wrightii biometry and biomass. Although the fauna have been similar in vegetated and nonvegetated areas, larvae and phytal specimens occurred only in vegetated areas. Despite the heterogeneous environmental scenarios, the four studied sites had a similar seasonal variation, also promoting similar seasonal alterations in the meadows. In all sites, the shoot density was higher in the dry season (t= 0,302; df = 88; p = 0,710), whereas biometry (t= 2,909; df = 62; p = 0,000) and biomass (t= -1,566; gl = 91; p = 0,119) were higher during the rainy season. The variable that best explained the variations of these meadows was the time of emersion (r = 0,813). The habitat and the seasonality had a significant influence on the biology and macrobiota associated with H. wrightii. The seasonal variations found suggested a strong relationship with the winds and rainfall regional patterns, which should also be monitored with the meadows, especially facing the expected climate alterations in semiarid region.